PENEGAKAN HUKUM TERHADAP PENGENDARA YANG MENGALIH FUNGSIKAN MOBIL PRIBADI MENJADI ANGKUTAN UMUM TRAYEK BENGKALIS-PEKANBARU - M. Tri Riansyah; Ardiansah; Andrizal (Smart Education, 2026)
Abstract: Legally, the conversion of private cars into public transportation without a permit is contrary to Article 173 paragraph (1) of Law Number 22 of 2009. Even though there are clear legal provisions, the practice of operating public transportation without a permit continues on the Bengkalis-Pekanbaru route. Regulation of private cars converted into public transportation has not provided a deterrent effect. In the process of law enforcement regarding transportation business permits for the conversion of private cars into public transportation is still weak, this is more due to supervision and coordination in the field playing a very important role. Researchers are interested in conducting a sociological legal research study with the title